The antitumor effect of hinesol, extract from Atractylodes lancea (Thunb.) DC. by proliferation, inhibition, and apoptosis induction via MEK/ERK and NF‐κB pathway in non–small cell lung cancer cell lines A549 and NCI‐H1299. Issue 11 (24th July 2019) - Guo, Weiqiang; Liu, Songbai; Ju, Xin; Du, Jiahui; Xu, Bin; Yuan, Hongxia; Qin, Fenju; Li, Liangzhi
Abstract: Lung cancer (especially, non–small cell lung cancer [NSCLC]) is one of the most malignant cancers in the world. Hinesol is the major component of the essential oil of Atractylodes lancea ( Thunb. ) DC and possesses the most promising anticancer function. However, the effects and molecular mechanism of hinesol on antiproliferation in NSCLC cells has not been well understood. In this study, we found that hinesol effectively inhibited the A549 and NCI‐H1299 cells in a dose‐ and time‐dependent manner by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazoliumbromide assay. In addition, hinesol induced cell cycle arrest at G0/G1 phase and apoptosis assessed by flow cytometry in A549 cells. Furthermore, Western blot analysis showed that hinesol decreased phosphorylation of mitogen‐activated protein kinase, extracellular signal‐regulated kinase, IκBα, and p65 inhibited the expressions of Bcl‐2, cyclin D1 and upregulated the expression of Bax. Based on these results, hinesol might be a potential drug candidate of anti‐NSCLC for therapy. Abstract : We evaluated the antitumor effect molecular mechanism of hinesol in the A549 and NCI‐H1299 cells. We demonstrated that hinesol effectively inhibited cell growth, arrested cell cycle at the G1/G0 phase, and induced apoptosis via downregulating the ERK and nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐kB) pathway.